COVID-19 and Eye Banking: Ongoing Impacts of the Pandemic. Issue 1 (17th January 2023) - Ballouz, Dena; Issa, Rafik; Sawant, Onkar B.; Hurlbert, Susan; Titus, Michael S.; Zhou, Yunshu; Musch, David C.; Majmudar, Parag A.; Kumar, Ashok; Mian, Shahzad I.
Abstract : Supplemental Digital Content is Available in the Text. Abstract : Purpose: The purpose of this study was to assess the impact of ongoing waves of the COVID-19 pandemic and resulting guidelines on the corneal donor pool with resumption of clinical operations. Methods: A retrospective analysis of donors deemed eligible for corneal transplantation at an eye bank from July 1, 2020, through December 31, 2021. Donors ineligible due to meeting Eye Bank Association of America (EBAA) COVID-19 guidelines or a positive postmortem COVID-19 testing were examined. The correlation between COVID-19 rule outs and state COVID positivity was calculated. The number of scheduled surgeries, suitable corneas, imports, and international exports was compared with a pre-COVID period. Postmortem testing was reduced for the final 5 months of the study, and numbers were compared before and after the policy change. Results: 2.85% of referrals to the eye bank were ruled out because of EBAA guidelines. 3.2% of postmortem tests were positive or indeterminate resulting in an ineligible tissue donor (0.42% of referrals). Over the 18-month period, there was a 4.30% shortage of suitable corneas compared with transplantation procedures. There was a significant correlation between postmortem testing and state COVID-19 positivity (r = 0.37, P <0.01), but not with EBAA guidelines (r = 0.19, P = 0.07). When postmortem testing was reduced, significantly more corneas were exported internationally. Conclusions: Although corneal transplant procedures were back to normal levels, there was a shortage of suitable corneal tissue. The discontinuation of postmortem testing was associated with a significant increase in international exports of corneal donor tissue.